Evolution of technical-economic indicators for Andalusian grazing dairy goats (2006-2008) - Castel J.M.; Mena Y.; Ruíz F.A.; Moya J.; Camúñez J. (Economic, social and environmental sustainability in sheep and goat production systems, 2011)
The aim of this work is to analyse the evolution of 10 technical-economic indicators during the period 2006-2008 in 6 pastoral farms of Andalusia (Spain) in order to observe the most determinant factors for the viability of systems. For the technical-economic analysis, an adaptation of the FAO/CIHEAM indicators list has been used. Values of indicators for each year and also for the whole of the period have been obtained. By consequence of increases of quantity and price of feed, economic margins of farms decreased from 2006 to 2008. Although the milk prices also increased, the proportion of the increase was less than in the feed price. While in 2008 the family net margin and, overall, the business net margin per litre of milk sold, were very low, the family net margin per unit of family labour was fairly acceptable. The meaning of this situation is that, at present, farms can survive because a part of the pay of family workers is used to purchase feed. Several regression analyses have been made. Only in two cases is there a significant level: the business net margin per litre of milk sold in comparison to the milk sold per goat and the family net margin per unit of family labour in comparison to the total labour.
7. Proceedings of the International Seminar of the Sub-Network on Production Systems of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2010/11/10-12, Zaragoza (Spain)